Laminated film and method for producing same

JP7641119B2Active Publication Date: 2025-03-06TORAY ADVANCED FILM CO LTD
View PDF 30 Cites 0 Cited by

Patent Information

Application Number
JP2020544677
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-19
Filing Date
2020-08-20
Publication Date
2025-03-06
Estimated Expiration
2040-08-20

AI Technical Summary

Benefits of technology

【0012】 本発明により、光学シート表面に対して初期粘着力、粘着昂進の抑制、加熱後の浮きの抑制および被着体に対する汚染の抑制のバランスに高度に優れる積層フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641119000001
    Figure 0007641119000001
  • Figure 0007641119000002
    Figure 0007641119000002
Patent Text Reader

Abstract

Provided is a layered film that strikes a highly excellent balance between the initial adhesive force onto an optical sheet surface, suppression of an increase in adhesion, suppression of lifting after heating, and suppression of contamination onto the adherend. The layered film has a resin layer (b) on one surface of a base material layer (a), and the resin layer (b) is a resin composition containing a hydrogenated copolymer composition and a tackifying resin. The hydrogenated copolymer composition satisfies conditions (1) to (3). (1) The hydrogenated copolymer composition is constituted from a polymer block having a vinyl aromatic monomer unit as the main body and a polymer block having a conjugated diene monomer unit as the main body, the polymer block having a conjugated diene monomer unit as the main body being present at each end. (2) The content of the vinyl aromatic monomer unit in the entirety of the hydrogenated copolymer composition is 5 to 30% by weight. (3) The melt flow rate of the hydrogenated copolymer composition is 3 to 30 g / 10 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate film having an excellent balance of initial adhesion to the surface of an optical sheet, suppression of adhesion increase, suppression of lifting after heating, and suppression of contamination of an adherend, and a method for producing the same. [Background technology]

[0002] Products made of various materials such as synthetic resins, metals, and glass are often treated with a material to protect the surface in order to prevent scratches and dirt that occur during processing, transportation, and storage. A typical material for protecting the surface is a protective film, and in general, a laminated film with an adhesive layer formed on a supporting substrate is used, and the adhesive layer surface is attached to an adherend and covered with the supporting substrate to protect the surface. In addition, these laminated films are required to have a moderately strong adhesive force between the adhesive layer and the adherend. This moderate strength refers to a strength that does not naturally peel off or fall off due to light vibration or impact, and a strength that allows smooth peeling without leaving an adhesive layer on the surface of the adherend when peeling off.

[0003] In recent years, liquid crystal displays and touch panel devices have become widespread, and these are composed of a large number of components such as optical sheets made of synthetic resins. Since defects such as optical distortion must be reduced as much as possible for such optical sheets, protective films are often used to prevent scratches and dirt that can cause defects.

[0004] Required properties of a protective film include not easily peeling off from the substrate when subjected to environmental changes such as temperature and humidity or small stresses, not increasing the adhesive strength (i.e., not becoming more adhesive) due to an increase in the contact area between the substrate and the adhesive layer caused by external factors such as time and temperature, and not leaving any adhesive or adhesive components on the substrate when peeled off from the substrate.

[0005] Among the above optical sheets, for example, in the case of a member having an uneven surface such as a diffusion plate, a prism sheet, or even a diffusion surface having various shapes formed on the back surface of a prism sheet, the adhesive layer may not conform sufficiently to the uneven surface immediately after the protective film is attached, and the desired adhesive strength may not be obtained, resulting in peeling. To address this issue, a method of softening the adhesive layer or a method of increasing adhesive strength by using a tackifier are known.

[0006] Patent Document 1 describes an adhesive resin composition and a protective film using the same. However, this protective film is prone to partial peeling (sometimes referred to as floating) when heated after being attached to an adherend, so it is necessary to contain a large amount of tackifier, and if the adhesive layer contains a large amount of tackifier, the adhesive layer is likely to remain on the surface of the adherend when the adhesive film is peeled off, resulting in a problem of the adherend being contaminated by the adhesive layer.

[0007] Patent Document 2 describes a pressure-sensitive adhesive composition and a surface protection film that contain a copolymer or a hydrogenated product thereof (hereinafter, hydrogenation may be referred to as hydrogenation) and a fatty acid amide having an acid value of 1 to 7. However, there are problems in that the composition partially peels off when heated after being attached to an adherend, and the fatty acid amide bleeds out (a phenomenon in which additives used in producing the film rise to the surface of the film over time), contaminating the process, the formed surface protection film, and even the adherend to which it is attached. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2019 / 044637 [Patent Document 2] JP 2012-1630 A Summary of the Invention [Problem to be solved by the invention]

[0009] The object of the present invention is to solve the above-mentioned problems, that is, to provide a laminated film that is excellent in the balance of initial adhesion to the surface of an optical sheet, suppression of adhesion increase, suppression of lifting after heating, and suppression of contamination of an adherend. [Means for solving the problem]

[0010] The above problems can be solved by the present invention described below.

[0011] A laminate film having a resin layer (b) on one surface of a base layer (a), the resin layer (b) being a resin composition containing a hydrogenated copolymer composition and a tackifier resin, the hydrogenated copolymer composition satisfying the following (1) to (3): (1) The hydrogenated copolymer composition comprises a polymer block mainly composed of vinyl aromatic monomer units and a polymer block mainly composed of conjugated diene monomer units, and has a polymer block mainly composed of conjugated diene monomer units at its terminal. (2) The content of vinyl aromatic monomer units in the entire hydrogenated copolymer composition is 5 to 30% by weight. (3) The hydrogenated copolymer composition has a melt flow rate of 3 to 30 g / 10 min. The present invention also provides the method for producing the laminated film, wherein the base layer (a) and the resin layer (b) are formed by melt co-extrusion. Effect of the Invention

[0012] The present invention can provide a laminate film that is highly excellent in balance between initial adhesion to the surface of an optical sheet, suppression of adhesion increase, suppression of lifting after heating, and suppression of contamination of an adherend. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In the present invention, the naming of each monomer unit constituting the copolymer is based on the naming of the monomer from which the monomer unit is derived. For example, a "vinyl aromatic monomer unit" means a structural unit of a polymer resulting from polymerization of a vinyl aromatic compound, which is a monomer. The vinyl aromatic monomer unit is bonded to other monomer units via the vinyl group of the vinyl aromatic compound.

[0014] In addition, the term "conjugated diene monomer unit" refers to a structural unit of a polymer resulting from the polymerization of a conjugated diene compound, which is a monomer. The conjugated diene monomer unit is bonded to another monomer unit through one of the two double bonds of the conjugated diene compound (1,2-bond or 3,4-bond), or is bonded to another monomer unit through both of the two double bonds of the conjugated diene compound (1,4-bond).

[0015] The "vinyl aromatic compound" constituting the "vinyl aromatic monomer unit" is not limited to the following, but examples thereof include styrene, α-methylstyrene, p-methylstyrene, divinylbenzene, 1,1-diphenylethylene, N,N-dimethyl-p-aminoethylstyrene, N,N-diethyl-p-aminoethylstyrene, etc. Among these, from the viewpoint of availability and productivity, styrene, α-methylstyrene, and p-methylstyrene are preferred. Among these, styrene is particularly preferred. These may be used alone or in combination of two or more.

[0016] The "conjugated diene compound" constituting the "conjugated diene monomer unit" is a diolefin having a pair of conjugated double bonds. Examples of the conjugated diene compound include, but are not limited to, 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, and farnesene. Preferred diolefins include 1,3-butadiene and isoprene. These may be used alone or in combination of two or more.

[0017] A coupling agent is preferably used in the hydrogenated copolymer composition, and the coupling agent is a polyfunctional compound that radially bonds the linear vinyl aromatic copolymer. The coupling agent is not particularly limited, but may be, for example, a polyalkenyl coupling agent. A suitable polyalkenyl coupling agent may be, for example, divinylbenzene, and m-divinylbenzene is preferred. In addition, the coupling agent may be, for example, tetraalkoxysilanes such as tetraethoxysilane and tetramethoxysilane, alkyltrialkoxysilanes such as methyltrimethoxysilane, dialkyldialkoxysilanes such as dimethyldimethoxysilane, carboxylic acid ester compounds such as ethyl benzoate and methyl benzoate, and diglycidyl aromatic epoxy compounds such as diglycidyl ethers derived from the reaction of bisphenol A with epichlorohydrin.

[0018] The hydrogenated copolymer composition of the present invention is composed of a polymer block mainly made of vinyl aromatic monomer units and a polymer block mainly made of conjugated diene monomer units, and has a polymer block mainly made of conjugated diene monomer units at the end. That is, when the polymer block mainly made of vinyl aromatic monomer units is A and the polymer block mainly made of conjugated diene monomer units is B, the composition has the structural formula BAB. Furthermore, the composition has the structural formula BABX by the coupling agent, and the structural formula (BAB)nX (n=2-4) in which the block structures of (BAB) are radially bonded. Here, X is a residue of the coupling agent used. By disposing the polymer block mainly made of conjugated diene monomer units at the end, it is possible to suppress lifting after heating.

[0019] The content of the vinyl aromatic monomer unit in the hydrogenated copolymer composition of the present invention is 5 to 30% by weight, preferably 6 to 20% by weight, and more preferably 8 to 12% by weight, based on the composition. If the content of the vinyl aromatic monomer unit exceeds 30% by weight, the initial adhesive strength decreases, and if the content of the vinyl aromatic monomer unit is less than 5% by weight, the adhesion promotion and the staining become worse.

[0020] The content of the vinyl aromatic monomer unit in the hydrogenated copolymer composition of the present invention can be measured by an ultraviolet spectrophotometer as described in the Examples below. Since the content of the vinyl aromatic monomer unit is almost the same before and after hydrogenation, it may be grasped by the content of the vinyl aromatic monomer unit in the copolymer before hydrogenation.

[0021] The ratio of double bonds in the conjugated diene monomer unit contained in the hydrogenated copolymer composition of the present invention (hereinafter sometimes referred to as hydrogenation ratio) is preferably 81 mol% or more, more preferably 85 mol% or more, and even more preferably 90 mol% or more. If it is less than 81 mol%, adhesion increases and adhesive residue may occur on the adherend.

[0022] The hydrogenation rate can be controlled, for example, by adjusting the amount of catalyst and the amount of hydrogen fed during hydrogenation. The hydrogenation rate can be controlled, for example, by adjusting the amount of catalyst and the amount of hydrogen fed during hydrogenation, pressure, temperature, etc. The hydrogenation rate can be measured by the method described in the Examples below.

[0023] The melt flow rate (hereinafter sometimes abbreviated as "MFR"; based on ISO 1133) of the hydrogenated copolymer composition in the present invention is 3 to 30 g / 10 min, preferably 5 to 20 g / 10 min, and more preferably 6 to 16 g / 10 min, under the conditions of a temperature of 230°C and a load of 21.17 N (2.16 kgf). If the MFR exceeds 30 g / 10 min, the initial adhesive strength becomes strong, the adhesiveness increases significantly, and adhesive residue also occurs. If the MFR is less than 3 g / 10 min, lifting occurs after heating. The MFR of the hydrogenated copolymer composition can be controlled by adjusting the polymerization conditions such as the amount of monomer added, polymerization time, temperature, and polymerization initiator, and can be measured by the method described in the examples below.

[0024] The resin layer (b) in the present invention contains a tackifier resin for the purpose of improving the initial adhesive strength. There is no particular limitation as long as the resin can impart viscosity to the laminated film of the present invention, and for example, it is preferably at least one resin selected from the group consisting of aliphatic petroleum resins, aromatic petroleum resins, aliphatic-aromatic petroleum resins, alicyclic petroleum resins, terpene resins, terpene phenol resins, rosin resins, alkylphenol resins, and xylene resins. Hydrogenated products obtained by hydrogenating these unsaturated bonds can also be used. More preferred are aliphatic petroleum resins, aromatic petroleum resins, aliphatic-aromatic petroleum resins, alicyclic petroleum resins, terpene resins, and terpene phenol resins, and most preferred are aromatic petroleum resins and terpene phenol resins.

[0025] The tackifier resin may be used alone or in combination of two or more kinds. The content of the tackifier resin in the resin composition of the resin layer (b) in the present invention is preferably 3 to 30% by weight, more preferably 5 to 20% by weight. If the content of the tackifier resin is less than 3% by weight, the desired initial adhesive strength cannot be obtained, and if it exceeds 30% by weight, the adhesion increases so much that adhesive residue is left on the adherend.

[0026] The resin composition of the resin layer (b) in the present invention may further contain a hydrogenated styrene-based elastomer having a structure other than the specific hydrogenated copolymer composition in the present invention described above in an amount up to 50% by weight based on the resin composition of the resin layer (b).

[0027] Representative examples of the hydrogenated styrene-based elastomer include, but are not limited to, styrene-conjugated diene copolymers such as styrene-butadiene copolymer (SBR), styrene-isoprene-styrene copolymer (SIS), and styrene-butadiene-styrene copolymer (SBS), as well as hydrogenated products thereof (e.g., hydrogenated styrene-butadiene copolymer (HSBR) and styrene-ethylene-butylene-styrene copolymer (SEBS)), and styrene-isobutylene copolymers (e.g., styrene-isobutylene-styrene triblock copolymer (SIBS) and styrene-isobutylene diblock copolymer (SIB), or mixtures thereof).

[0028] The resin composition of the resin layer (b) in the present invention may contain stabilizers such as antioxidants and light stabilizers. In addition to the various materials described above, various additives may be added as necessary.

[0029] Examples of the additives include, but are not limited to, pigments such as red iron oxide and titanium dioxide; waxes such as paraffin wax, microcrystalline wax, and low molecular weight polyethylene wax; polyolefin-based or low molecular weight vinyl aromatic thermoplastic resins such as amorphous polyolefin and ethylene-ethyl acrylate copolymer; natural rubber; and synthetic rubbers such as polyisoprene rubber, polybutadiene rubber, styrene-butadiene rubber, ethylene-propylene rubber, chloroprene rubber, acrylic rubber, isoprene-isobutylene rubber, and polypentenamer rubber.

[0030] Specific examples of the synthetic rubber include those described in "Rubber and Plastic Compounding Chemicals" (edited by Rubber Digest Co., Ltd.).

[0031] The resin layer (b) in the present invention is formed as a resin composition comprising the specific hydrogenated copolymer composition in the present invention and a tackifier resin, laminated on the substrate layer (a).

[0032] The thickness of the resin layer (b) in the present invention is preferably 1 μm to 30 μm, more preferably 2 μm to 20 μm. If the thickness of the resin layer (b) exceeds 30 μm, the productivity is unstable, and if it is less than 1 μm, the adhesion to the adherend may deteriorate.

[0033] The material of the substrate layer (a) in the present invention is not particularly limited, and both non-polar and polar resins can be used. In terms of performance and cost, polyolefin resins are preferred as non-polar resins. The polyolefin resins contained in the substrate are not particularly limited, and include polyethylene resins such as ethylene homopolymers, ethylene-α-olefin copolymers, ethylene-(meth)acrylic acid copolymers, ethylene-(meth)acrylic acid ester copolymers, and ethylene-vinyl acetate copolymers, polypropylene resins such as propylene homopolymers, propylene-α-olefin copolymers, and propylene-ethylene copolymers, homopolymers or copolymers of conjugated dienes such as butene homopolymers, butadiene, and isoprene, and the like. Examples of the polyethylene resins include high-density polyethylene, medium-density polyethylene, and low-density polyethylene. The copolymerization form may be random, block, or terpolymer. The polyolefin resins may be used alone or in combination of two or more kinds. The polyethylene resins are obtained by using ethylene as the main component. The ratio of structural units derived from ethylene in 100% by weight of all structural units of the polyethylene resin is preferably 50% by weight or more, more preferably 70% by weight or more, and even more preferably 90% by weight or more. The polypropylene resin is obtained by using propylene as a main component. The ratio of structural units derived from propylene in 100% by weight of all structural units of the polypropylene resin is preferably 50% by weight or more, more preferably 70% by weight or more, and even more preferably 90% by weight or more. It is preferable that the base layer (a) in the present invention is mainly made of a polypropylene resin in terms of heat resistance, weather resistance, or adhesion to the resin layer (b).

[0034] The thickness of the substrate layer (a) in the present invention is preferably 10 μm or more and 150 μm or less, more preferably 15 μm or more and 80 μm or less, and most preferably 20 μm or more and 50 μm or less.

[0035] When the laminated film of the present invention is composed of only the substrate layer (a) and the resin layer (b), it is preferable to impart unevenness to the surface of the substrate layer (a) in order to suppress the adhesive strength between the surface of the substrate layer (a) and the surface of the resin layer (b) and to reduce the contact area with the resin layer (b). As a means for this, a resin incompatible with the resin used in the substrate layer (a) may be added, or organic or inorganic particles may be blended.

[0036] When the base layer (a) is mainly made of a polypropylene-based resin, the incompatible resin may be an α-olefin polymer having 4 or more carbon atoms, such as a 4-methylpentene-1-based polymer. Other examples include low-density polyethylene, high-density polyethylene, a copolymer of ethylene and a small amount of α-olefin, a copolymer of ethylene and vinyl acetate, polystyrene, an alicyclic olefin resin, a polyester-based resin, and a polyamide-based resin.

[0037] Examples of such organic particles include polyethylene, polystyrene, polymethyl methacrylate, etc. Examples of polyethylene particles include high molecular weight polyethylene fine particles "Mipelon" manufactured by Mitsui Chemicals, Inc., and crosslinked acrylic monodisperse particles MX-1500H manufactured by Soken Chemical & Engineering Co., Ltd. Examples of inorganic particles include silica and titanium oxide.

[0038] On the other hand, it is also possible to moderately suppress the adhesive strength of the surface with the resin layer (b) by adding a silicone-based release agent to the base layer (a). Examples of such silicone-based release agents include "EXFOLA" manufactured by Mitsui Fine Chemicals, Inc., BY27-201C and BY27-202H manufactured by Dow Toray Industries, Inc., and Perlane Y19220 and SiPP MB01 manufactured by Momentive Performance Materials Japan, LLC.

[0039] In the present invention, it is preferable to laminate a second resin layer (c) on the other surface of the base layer (a) in order to suppress adhesion between the resin layer (b) and the second resin layer (c).

[0040] The material constituting the second resin layer (c) in the present invention is not particularly limited, but is preferably the same composition as the base layer (a). From the viewpoints of productivity, cost, and release effect, it is preferable to add the above-mentioned incompatible resins, organic or inorganic particles, release agents, etc. to the second resin layer (c).

[0041] The thickness of the second resin layer (c) in the present invention is preferably 1 μm or more and 20 μm or less. If the thickness of the second resin layer (c) is less than 1 μm, the processability during film formation is poor, and if it exceeds 20 μm, it is likely to lead to an increase in cost as a laminate film.

[0042] Next, a method for producing the laminated film of the present invention will be described.

[0043] The method for producing the laminated film of the present invention is not particularly limited, but for example, in the case of a three-layer laminate structure of a resin layer (b), a base layer (a), and a second resin layer (c), the resin compositions constituting each layer are melt-extruded from individual extruders and laminated together in a die, so-called co-extrusion method, or a method in which the resin layer (b), the base layer (a), and the second resin layer (c) are melt-extruded separately and then laminated by a lamination method, etc. are mentioned. From the viewpoint of productivity, it is preferable to produce the laminated film by the co-extrusion method. The materials constituting each layer may be mixed with each other using a Henschel mixer or the like, or all or a part of the materials for each layer may be kneaded in advance. As for the co-extrusion method, known methods such as an inflation method and a T-die method are used, but from the viewpoint of excellent thickness accuracy and surface shape control, a hot melt co-extrusion method using a T-die method is particularly preferable.

[0044] The laminated film of the present invention can be used as a surface protection film for preventing scratches and dirt adhesion during the production, processing, and transportation of synthetic resin plates, metal plates, glass plates, etc., and is preferably used as a surface protection film for optical applications having uneven surfaces such as diffusion plates and prism sheets. EXAMPLES

[0045] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples. The measurement methods and evaluation methods of physical properties applied to the examples and comparative examples are described below.

[0046] (1) Hydrogenation rate of double bonds derived from the conjugated diene compound of the hydrogenated copolymer composition The block ratio and vinyl in the hydrogenated copolymer composition were measured by nuclear magnetic resonance spectroscopy (NMR) under the following conditions. In the measurement, the liquid after the hydrogenation reaction was poured into a large amount of methanol, and the hydrogenated copolymer composition was precipitated and recovered. The hydrogenated copolymer composition was then extracted with acetone, and the extract was vacuum dried, 1 This was used as a sample for H-NMR measurement under the following measurement conditions. (Measurement conditions) Measuring equipment: JNM-LA400 (JEOL) Solvent: Deuterated chloroform Measurement samples: Samples taken before and after hydrogenation of the polymer Sample concentration: 50mg / mL Observation frequency: 400MHz Chemical shift standard: CDCl3 (deuterium chloroform) Pulse Delay: 2.904 seconds Number of scans: 256 Pulse width: 45° Measurement temperature: 26℃.

[0047] (2) Melt flow rate (MFR) of hydrogenated copolymer composition The MFR (g / 10 min) of the hydrogenated copolymer composition was measured in accordance with ISO 1133 under conditions of a temperature of 230° C. and a load of 21.17 N (2.16 kgf).

[0048] (3) Content of vinyl aromatic monomer units in hydrogenated copolymer composition A certain amount of the hydrogenated copolymer composition was dissolved in chloroform and measured with an ultraviolet spectrophotometer (Shimadzu Corporation, UV-2450). Based on the peak intensity at the absorption wavelength (262 nm) due to the vinyl aromatic compound (styrene), the content of the vinyl aromatic monomer unit in the hydrogenated copolymer composition was calculated using a calibration curve.

[0049] (4)Initial adhesive strength Each laminate film, which had been temperature- and humidity-conditioned for 24 hours under conditions of a temperature of 23°C and a relative humidity of 50%, was attached to the lens surface of a prism sheet so as to cover the lens surface using a roll press machine (Yasuda Seiki Seisakusho Co., Ltd. special pressure roller (hardness A80, weight 2 kg)) at a bonding pressure of 0.35 MPa and a bonding speed of 3 m / min. After that, the film was stored for 24 hours at a temperature of 23°C and a relative humidity of 50%, and then the adhesive strength was evaluated. The prism sheet used was made of acrylic resin with a thickness of 95 μm and a gap between the prism ridges of 25 μm.

[0050] The adhesive strength was measured using a tensile tester (Orientec Co., Ltd. universal testing machine "Tensilon") at a peel speed of 300 mm / min and a peel angle of 180 degrees. The measurement was carried out five times, and the average value was taken as the initial adhesive strength. (Judgment criteria) Adhesive strength (initial) Excellent: 10mN / 25mm or more, less than 100mN / 25mm Good: 100mN / 25mm or more, less than 300mN / 25mm Defective: Less than 10mN / 25mm, more than 300mN / 25mm.

[0051] (5) Adhesive strength over time (adhesive strength increases) Using the same method as in the (4) Initial Adhesion Test, each laminate film was attached to the lens surface of the prism sheet so as to cover the lens surface, and then stored in a hot air oven controlled at 50°C for 72 hours, and then further stored at a temperature of 23°C and a relative humidity of 50% for 24 hours, after which the adhesion was evaluated.

[0052] The adhesive strength was measured using a tensile tester (Orientec's universal testing machine "Tensilon") at a peel speed of 300 mm / min and a peel angle of 180 degrees. The measurement was performed three times, and the average value was taken as the adhesive strength over time. The peel strength measured in this way was taken as the adhesive strength over time, and the rate of change in adhesive strength over time (adhesion increase rate) from the initial adhesive strength was calculated using the following formula. Adhesion increase rate (%) = (adhesion strength over time / initial adhesion strength) x 100 (%) (Judgment criteria) adhesive agitation rate Excellent: 80% or more, less than 150% Good: 150% or more, less than 250% Defective: 250% or more.

[0053] (6) Heat float evaluation Using the same method as in the (4) Initial Adhesion Test, each laminate film was attached to the lens surface of the prism sheet so as to cover the lens surface. After that, it was stored in a hot air oven controlled at 50°C for 72 hours, and then stored at a temperature of 23°C and a relative humidity of 50% for 24 hours, after which it was visually evaluated whether the surface protection sheet had lifted off the prism sheet. The case where no lifting was observed was evaluated as good, and the case where lifting was observed was evaluated as poor.

[0054] (7) Evaluation of adhesive residue (contamination) Using the same method as in the (4) Initial Adhesion Test, each surface protection sheet was attached to the lens surface of the prism sheet so as to cover the lens surface. After leaving it in an environment of 60°C for 30 minutes, the surface protection film was peeled off and the presence or absence of adhesive residue on the prism sheet was visually evaluated. (Judgment criteria) Good: No adhesive residue can be seen on the prism sheet. Poor: Glue residue can be observed on the prism sheet.

[0055] (Production of Hydrogenated Copolymer Composition) (Production example) Using a tank reactor equipped with a stirrer and a jacket, cyclohexane was used as the solvent, and n-butyl lithium (hereinafter sometimes referred to as Bu-Li) was used as the polymerization catalyst. First, a specified amount of butadiene monomer (I) was added to complete the polymerization, then a specified amount of styrene monomer was added to complete the polymerization, and then a specified amount of butadiene monomer (II) was added to complete the polymerization. After the polymerization was completed, a coupling agent, tetraethoxysilane, was added to crosslink part of the butadiene-styrene-butadiene copolymer, and a mixture of the butadiene-styrene-butadiene copolymer and its crosslinked product (copolymer composition) was obtained.

[0056] Thereafter, a predetermined amount of biscyclopentadienyltitanium chloride and trimethylaluminum were added as hydrogenation catalysts to the obtained polymerization solution, and the double bonds derived from butadiene were hydrogenated. After the reaction was completed, octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as an antioxidant to obtain the desired hydrogenated copolymer composition (hydrogenated product in the following examples). The composition and physical properties of the obtained hydrogenated copolymer composition are shown in Table 1.

[0057] Example 1 As a hydrogenated copolymer composition, 85% by weight of the hydrogenated product 1 obtained in Production Example was dry-blended with 15% by weight of aromatic hydrocarbon resin "FTR" 8100 manufactured by Mitsui Chemicals, Inc. to form the resin layer (b).

[0058] For the base layer (a), "Prime Polypro" F113G manufactured by Prime Polymer Co., Ltd., which is an isotactic polypropylene (homopolypropylene) having an MFR of 3.0 g / 10 min, was used.

[0059] The resins of the resin layer (b) and base layer (a) were fed into a two-type, two-layer T-die film-making machine equipped with two single-screw extruders with a compression ratio of 4.2 and L / D=25, and cast so that the resin layer (b) side was in contact with a metal cooling roll whose temperature was controlled at 30°C. The resin was then cooled and solidified to form a film, yielding a laminated film consisting of a resin layer (b) 4 μm thick, a base layer (a) 36 μm thick, and an overall thickness of 40 μm.

[0060] Example 2 A film having an overall thickness of 40 μm was obtained in the same manner as in Example 1, except that the composition of the resin layer (b) in Example 1 was changed as follows. Hydrogenated product obtained in the production example 2: 85% by weight ·“FTR”8100:15% by weight.

[0061] Example 3 A film having an overall thickness of 40 μm was obtained in the same manner as in Example 1, except that the composition of the resin layer (b) in Example 1 was changed as follows. Hydrogenated product obtained in the production example 3: 85% by weight ·“FTR”8100:15% by weight.

[0062] Example 4 A film having an overall thickness of 40 μm was obtained in the same manner as in Example 1, except that the composition of the resin layer (b) in Example 1 was changed as follows. Hydrogenated product obtained in the production example 4: 85% by weight ·“FTR”8100:15% by weight.

[0063] Example 5 A film having an overall thickness of 40 μm was obtained in the same manner as in Example 1, except that the composition of the resin layer (b) in Example 1 was changed as follows. Hydrogenated product obtained in the production example 5: 85% by weight ·“FTR”8100:15% by weight.

[0064] Example 6 A film having an overall thickness of 40 μm was obtained in the same manner as in Example 1, except that the composition of the resin layer (b) in Example 1 was changed as follows. Hydrogenated product obtained in the production example 1: 85% by weight Terpene phenol resin YS Polystar TH130 manufactured by Yasuhara Chemical Co., Ltd.: 15% by weight.

[0065] Example 7 A laminate film having a total thickness of 40 μm was obtained in the same manner as in Example 1, except that the thickness of the resin layer (b) in Example 1 was changed to 25 μm and the thickness of the base layer (a) to 15 μm.

[0066] Example 8 A laminate film having a total thickness of 40 μm was obtained in the same manner as in Example 1, except that the thickness of the resin layer (b) in Example 1 was changed to 2 μm and the thickness of the base layer (a) to 38 μm.

[0067] Example 9 In addition to the composition shown in Example 1, the composition shown below was used as the second resin layer (c) on the opposite side of the substrate layer (a) to where the resin layer (b) was formed. The resins of the above resin layer (b), substrate layer (a) and second resin layer (c) were fed into a three-type three-layer T-die film-making machine equipped with three short-axis screw extruders with a compression ratio of 4.2 and L / D=25, and cast so that the resin layer (b) side was in contact with a metal cooling roll whose temperature was controlled at 30°C. The film was then cooled and solidified to form a film, and a three-layer laminate film consisting of a resin layer (b) thickness of 4 μm, a total thickness of the substrate layer (a) and the second resin layer (c) of 36 μm, and an overall thickness of 40 μm was obtained. Block PP resin "Topilene" J640F manufactured by Hyosung Japan Co., Ltd.: 90% by weight -Mitsui Chemicals Fine Co., Ltd. Olefin-silicone copolymer "EXFOLA" PP masterbatch: 10% by weight Comparative Example 1 A film having an overall thickness of 40 μm was obtained in the same manner as in Example 1, except that the composition of the resin layer (b) in Example 1 was changed as follows. Hydrogenated product obtained in the production example 6: 85% by weight ·“FTR”8100:15% by weight.

[0068] Comparative Example 2 A film having an overall thickness of 40 μm was obtained in the same manner as in Example 1, except that the composition of the resin layer (b) in Example 1 was changed as follows. Hydrogenated product obtained in the production example 7: 85% by weight ·“FTR”8100:15% by weight.

[0069] Comparative Example 3 A film having an overall thickness of 40 μm was obtained in the same manner as in Example 1, except that the composition of the resin layer (b) in Example 1 was changed as follows. Hydrogenated product obtained in the production example 8: 85% by weight ·“FTR”8100:15% by weight.

[0070] Comparative Example 4 A film having an overall thickness of 40 μm was obtained in the same manner as in Example 1, except that the composition of the resin layer (b) in Example 1 was changed as follows. Hydrogenated product obtained in the production example 9: 85% by weight ·“FTR”8100:15% by weight.

[0071] Comparative Example 5 A film having an overall thickness of 40 μm was obtained in the same manner as in Example 1, except that the composition of the resin layer (b) in Example 1 was changed as follows. Hydrogenated product obtained in the production example 1: 100% by weight.

[0072] Comparative Example 6 A film having an overall thickness of 40 μm was obtained in the same manner as in Example 1, except that the composition of the resin layer (b) in Example 1 was changed as follows. JSR Corporation hydrogenated styrene butadiene rubber "DYNARON" 1321P (hydrogenated copolymer with no butadiene monomer at the end): 85% by weight ·“FTR”8100:15% by weight.

[0073] [Table 1]

[0074] [Table 2]

[0075] Examples 1 to 8 were highly excellent in the balance of initial adhesion to the optical sheet surface, suppression of adhesion increase, suppression of lifting after heating, and suppression of contamination of the adherend. On the other hand, in Comparative Examples 1, 4, 5, and 6, the laminated film floated up and peeled off when heated after being attached to the adherend. In Comparative Examples 2 and 3, the adhesion increased significantly when heated after being attached to the adherend, causing the adhesive to remain on the surface of the adherend, resulting in a problem of adhesive residue (contamination) on the surface of the adherend. [Industrial Applicability]

[0076] The laminated film of the present invention can be preferably used not only as a surface protection film for preventing scratches and stains on an adherend having an uneven surface, but also as a surface protection film for various products made of various materials such as synthetic resins, metals, and glass.

Claims

1. The laminate film has a resin layer (b) on one surface of a base layer (a), the resin layer (b) being a resin composition containing a hydrogenated copolymer composition and a tackifier resin, and the hydrogenated copolymer composition satisfies the following (1) to (3): (1) The hydrogenated copolymer composition is constituted by a polymer block A mainly composed of vinyl aromatic monomer units and a polymer block B mainly composed of conjugated diene monomer units, and has a structural formula of B-A-B. (2) The content of vinyl aromatic monomer units in the entire hydrogenated copolymer composition is 5 to 30% by weight. (3) The hydrogenated copolymer composition has a melt flow rate of 3 to 30 g / 10 min.

2. 2. The laminate film according to claim 1, wherein 81 mol % or more of the double bonds of the conjugated diene monomer units contained in the hydrogenated copolymer composition of the resin layer (b) are hydrogenated.

3. 3. The laminated film according to claim 1, wherein the resin layer (b) has a thickness of 1 to 30 μm.

4. The laminated film according to any one of claims 1 to 3, wherein the tackifier resin of the resin layer (b) is at least one resin selected from the group consisting of aliphatic petroleum resins, aromatic petroleum resins, aliphatic / aromatic petroleum resins, alicyclic petroleum resins, terpene resins, terpene phenol resins, rosin resins, alkylphenol resins, and xylene resins.

5. 5. The laminated film according to claim 1, wherein the content of the tackifier resin in the resin composition of the resin layer (b) is 3 to 30% by weight.

6. The laminate film according to any one of claims 1 to 5, further comprising a second resin layer (c) on the other surface of the base layer (a).

7. The method for producing a laminated film according to any one of claims 1 to 5, wherein the base layer (a) and the resin layer (b) are formed by melt co-extrusion.

8. A method for producing a laminated film as described in claim 6, wherein the base material layer (a), the resin layer (b) and the second resin layer (c) are formed by melt co-extrusion.

9. A method for producing the laminated film according to any one of claims 1 to 6, The hydrogenated copolymer composition of the resin layer (b) is obtained by completing the polymerization of butadiene monomer, then completing the polymerization of styrene monomer, and further completing the polymerization of butadiene monomer, adding a coupling agent to crosslink a part of a butadiene-styrene-butadiene copolymer, and adding a hydrogenation catalyst to the obtained copolymer and the crosslinked product to hydrogenate the double bonds, in a method for producing a laminated film.

10. The laminate film according to any one of claims 1 to 6, which is used as a protective film for a prism surface.

Citation Information

Patent Citations

  • Method and installation for continuous casting

    JP1987006749A

  • Surface protecting film

    JP1994240216A

  • Surface protection film

    JP2001234142A

  • Hydrogenated styrenic resin composition

    JP2008239861A

  • Pressure-sensitive adhesive composition and surface-protecting film

    JP2008274212A